A Novel Pre-Synchronization Control Method Based on Open-Loop Phase Detection for the Maritime VSC-HVDC System - Shi, Jianquan; Wu, Dandan; Ge, Qiang; Qian, Yang (Frontiers in Energy Research, 2022)
The maritime island grids based on renewable energy is being rapidly developed, which poses a new challenge to the traditional pre-synchronization process of grid connection. Aiming at the problems of impulse current out of limit and long steady-state regulation time, a novel pre-synchronization control method is provided based on open-loop phase detection, which is realized by replacing the frequency detection method of the difference judgment part.The open-loop detection model of voltage phase and amplitude based on the synchronous rotating coordinate system is established first. Then the voltage phase is linearized to control the output frequency, and finally reduces the voltage deviation through the compensation of virtual power to achieve the effect of smooth grid connection. The novel pre-synchronization method has fast response speed and no regulator effect, which can synchronize the actual values of output voltage amplitude, phase and frequency. Simulation results verify the excellent performance of the proposed method in island stable operation and grid connection under disturbance.